In silico Docking and 3D-QSAR Studies of Novel N’-substituted-(pyrrolyl-phenoxy) Acetohydrazides as Enoyl-ACP Reductase Antagonists - Joshi, Shrinivas Dattatraya; Kumar, SR Prem; Kulkarni, Venkatarao H; Alshabi, Ali Mohamed; Shaikh, Ibrahim Ahmed; Aminabhavi, TM (Indian Journal of Pharmaceutical Education and Research, 2020)
In search of potent anti-mycobacterial agents, enoyl-ACP reductase enzyme found to be most probable due to its imperative role in type II fatty acid synthesis (FAS), while mycolic acid production in Mycobacterium tuberculosis (M. tuberculosis), which is the appropriate entity for the discovery of antimycobacterial agents due to its primary role in the metabolism. Hence, blocking of enoyl ACP reductase would be important to develop novel antitubercular drugs development. Pyrrole, which is one of the five membered heterocyclic moieties habitually institute in few of naturally occurring and organic products of various classes, plays a significant part in medicinal drug discovery. In this work, docking and 3D-QSAR (CoMFA and CoMSIA) studies were performed on a set of pyrrolyl phenoxy acetohydrazides. As per docking study, TYR158 and co-factor NAD+ are important amino acid residue at active site of enzyme for binding with the ligand. Among all the tested molecules, Compounds 4 and 28 have shown good docking scores of 7.08 and 8.85 respectively, steric and electrostatic field in CoMFA model displayed q2 = 0.511, r2 = 0.822 while that of CoMSIA model displayed q2 = 0.625, r2 = 0.764 with the SEE values of of 0.314 and 0.607. Docking study revealed complete structurally imperative binding topographies between the pyrrole scaffolds and enoyl ACP reductase enzyme. Our studies offered useful information and evidence for designing of molecules with enhanced InhA inhibition.
Keywords: Pyrrol-(1H-yl-phenoxy)acetohydrazides; Enoyl ACP reductase (InhA); Molecular Docking; 3D-QSAR; CoMFA; CoMSIA